2010
DOI: 10.1016/j.actamat.2010.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Plastic anisotropy of γ-TiAl revealed by axisymmetric indentation

Abstract: Single crystals of γ-TiAl cannot be grown in the near-stoichiometric compositions that are present inside two-phase γ/α 2 -microstructures with attractive mechanical properties. Therefore, the single crystal constitutive behavior of γ-TiAl was studied by nanoindentation experiments in single phase regions of these γ/α 2 -microstructures. The experiments were characterized by orientation microscopy and atomic force microscopy to quantify the orientation dependent mechanical response during nanoindentation. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 99 publications
(120 reference statements)
0
49
0
Order By: Relevance
“…Such tests correspond to mechanical characterization of an incidentally oriented grain in a polycrystalline or composite material. An excellent review of the literature on indentation of single crystals has recently been given in [5], therefore, we summarize here only those results of previous works that are most closely related to the present study.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Such tests correspond to mechanical characterization of an incidentally oriented grain in a polycrystalline or composite material. An excellent review of the literature on indentation of single crystals has recently been given in [5], therefore, we summarize here only those results of previous works that are most closely related to the present study.…”
Section: Introductionmentioning
confidence: 75%
“…This effect is particularly difficult to be accurately described in indentation testing of anisotropic materials like single crystals since the surface topography is then complex and orientation-dependent, also for axisymmetric indenters [4,5]. On the other hand, complex topography of the surface along with the indentation curve bear information of potential use for local mechanical characterization of anisotropic materials by detailed comparison with the results of numerical three-dimensional (3D) simulations, in particular, with the help of crystal plasticity FEM (finite element method) [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy of Ti-rich side alloys is highly pronounced irrespective of whether it is at room temperature (Werwer and Cornec 2006) or at high temperature (Wegmann et al 2000). Room temperature plastic anisotropy of similar Ti-rich TiAl lamellar single crystals has also been discussed in Zambaldi et al (2011), Zambaldi and Raabe (2010), and among others, where they showed that the maximum yield stress occurs when lamellar direction is perpendicular to the compression axis i.e φ = 90°, stress is the minimum when approximately φ = 45°, and at φ = 0°stress is in between (Brockman 2003, Fujiwara et al 1990). The ratio of the highest to the lowest values of yield stress is almost 8:1.…”
Section: Anisotropy In Ti-rich Sidementioning
confidence: 95%
“…The growing application has also been extended to petroleum, medical, and defense industries (Khan et al 2012;Tuninetti et al 2015). Since 1970s, this alloy system has been widely recognized as a possible basis for novel lightweight materials for high temperature applications (Zambaldi 2010). Experts are convinced that the alloy system has immense potential *Correspondence: helal.chowhury@ovgu.de 1 Graduate School for 'Micro-Macro Interactions in Structured Media and Particle Systems', Otto-von-Guericke University, 39106 Magdeburg, Germany Full list of author information is available at the end of the article that could revolutionize the world of aviation.…”
Section: The Family Of Ti-al Alloysmentioning
confidence: 99%
“…As the latter prevail during indention testing, this tool can be potentially used to assess the cross-hardening (multiple-glide) behavior of the crystal as well as its strain hardening saturation response occurring at larger strain levels. Continuum crystal plasticity has become a powerful scheme in describing single-crystal deformation responses under a variety of loading configurations including indentation (e.g., Eidel and Gruttmann, 2007;Liu et al, 2008;Alcalá et al, 2008;Casals and Forest, 2009;Chang et al, 2010;Zambaldi and Raabe, 2010;Saito et al, 2012;Alcalá and Esqué-de los Ojos, 2012). Hence, this modeling framework could be instrumental in the development of novel methodologies for the assessment of single-crystal uniaxial responses from microhardness measurements.…”
Section: Introductionmentioning
confidence: 99%